Single stage totally laparoscopic management of Barnard’s syndrome: the first such case report with review of literature - Gandhi, Hemangi; Joshi, Abhijit (International Surgery Journal, 2022)
Gall stone ileus is an uncommon however important complication of cholelithiasis. This condition is seen commonly in elderly females with comorbidities. It results from the passage of stone into the small bowel from the gall bladder through a cholecysto-duodenal fistula. Presenting symptoms include typical features of small bowel obstruction. Diagnosis can be made radiologically. Surgical management is the mainstay of treatment. The procedure can be done either in a single stage, where the stone retrieval is done through enterotomy followed by cholecystectomy and fistula repair; or in two stages, which comprise of enterolithotomy alone in stage 1 followed by interval cholecystectomy and fistula repair in stage 2. Laparoscopic single stage management enables definitive surgical therapy of the condition during a single hospital stay and under a single session of anaesthesia.